Riverine microplastic discharge along the southern Black Sea coast of Türkiye - Yahya Terzi; Rafet Çağrı Öztürk; Ahmet Raif Eryaşar; İlhan Yandi; Ahmet Şahin; Fatih Yılmaz; Kenan Gedik; Sedat Gündoğdu (Environmental Research Letters)
Rivers are critical pathways of microplastic (MP) pollution to marine environments, yet their contributions to the Black Sea remain understudied. This study evaluates the abundance and characteristics (polymer composition, shape, size, and color) of MPs discharged from 29 rivers flowing into the southern Black Sea. Using a plankton net with a 200 μ m mesh size, samples were collected from river mouths, revealing an average MP abundance of 9.63 ± 1.27 MP m ^−3 , ranging from 1.03 to 29.8 MP m ^−3 . Eastern Black Sea rivers exhibited significantly higher MP levels (11.0 ± 1.57 MP m ^−3 ) compared to western rivers (5.15 ± 1.25 MP m ^−3 ). Annual MP discharge to the Black Sea was estimated at 1.49 × 10 ^11 particles. Polyethylene terephthalate (PET, 59.3% ± 2.66%), polyethylene (PE, 20.8% ± 2.04%), and polypropylene (PP, 14.1% ± 2.36%) were the most common polymers, with PET and PE being significantly dominant. MP sizes ranged predominantly between 200–1000 μ m, and fibers constituted the majority of shapes (64.1%), followed by fragments (28.3%). White (36.8% ± 1.93%) and transparent (30.9% ± 2.39%) MPs were the most prevalent colors. While no significant differences in MP characteristics were detected between basins (NMDS and ANOSIM), this study emphasizes rivers as major pathways for MP pollution in the Black Sea. These findings underscore the urgent need for targeted mitigation strategies to safeguard marine ecosystems and biodiversity.